INTEGRATING SOCIAL SCIENCES AND HUMANITIES IN MEDICAL EDUCATION: A CASE FROM PAKISTAN - Ghias, Kulsoom; Khan, Kausar S.; Ali, Rukhsana; Kashif, Waqar; Khan, Murad M.; Sarfraz, Shajia (European Scientific Journal, ESJ, 2014)
Relationship between medical education and social sciences and humanities is an emerging field within health and medical sciences. How social sciences and humanities (SSH) consider their role in professional education in general and medical sciences in particular is yet to be explored jointly and systematically. This paper presents, as a case, how a private institution in Karachi, Pakistan, has consciously and systematically integrated SSH in its undergraduate and graduate education programs. SSH in this institution is grouped into two initiatives – Bioethics, and Humanities and Social Sciences. The paper describes what has been achieved over the last twenty years, including the challenges faced and overcome. It will explain how it became possible for the institution to go beyond the traditional practices of focusing only on medical sciences. Finally, the challenges faced in building partnerships between medical and social sciences will be discussed. Following an introduction that outlines the vision and mission of the institution that provided the space for integrating SSH in its medical education program, both at the undergraduate and graduate levels, the paper describes the content, pedgagical approaches, challenges and the way forward for (1) teaching of humanities and social sciences, (2) bioethics and (3) behavioural sciences in the undergraduate medical curriculum; and (4) social sciences in the Masters program of Community Health Sciences Department.